1999
DOI: 10.1038/sj.bjc.6690195
|View full text |Cite
|
Sign up to set email alerts
|

Cladribine with cyclophosphamide and prednisone in the management of low-grade lymphoproliferative malignancies

Abstract: The feasibility of combining cladribine with cyclophosphamide and prednisone in the management of indolent lymphoid malignancies was determined. Nineteen patients [nine chronic lymphocytic leukaemia (CLL), seven non-Hodgkin's lymphoma (NHL) and three macroglobulinaemia (M))] received cladribine 0.1 mg kg −1 per day as a subcutaneous bolus injection on days 1–3 (up to 5 injections) with intravenous cyclophosphamide 500 mg m −2 on day 1 and oral prednisone 40 mg m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 37 publications
0
32
0
Order By: Relevance
“…[50][51][52][53][54] Because alkylating agents and nucleoside analogues have been shown to be effective, combinations of these agents have been tested, and response rates of 58% to 88% have been observed. [55][56][57] The addition of rituximab to these agents has been well tolerated with little additional toxicity and appears to further increase the response rate. 58-60 Recent studies using the proteasome inhibitor bortezomib in combination with rituximab have found this combination to be effective.…”
Section: Choice Of Initial Therapymentioning
confidence: 99%
“…[50][51][52][53][54] Because alkylating agents and nucleoside analogues have been shown to be effective, combinations of these agents have been tested, and response rates of 58% to 88% have been observed. [55][56][57] The addition of rituximab to these agents has been well tolerated with little additional toxicity and appears to further increase the response rate. 58-60 Recent studies using the proteasome inhibitor bortezomib in combination with rituximab have found this combination to be effective.…”
Section: Choice Of Initial Therapymentioning
confidence: 99%
“…Future approaches to improving the CR rate and remission duration with front-line 2-CdA therapy may involve combination therapy with other chemotherapeutic agents. Several Phase I and II trials have piloted combinations of 2-CdA with mitoxantrone, [40][41][42] cyclophosphamide, 43,44 and chlorambucil. 45 However, in those initial trials, response rates from 28.5% to 90% (CR rate, 7.1-44%) appear similar to single-agent trials, and toxicities may be increased.…”
Section: Discussionmentioning
confidence: 99%
“…In the trials finished to date, alkylating drugs and anthracyclines with mitoxantrone were most often combined with either FAMP or with 2-CdA. [10][11][12][13][14][15][16][17][18]29,30 Our study is the first, to our knowledge, in which previously Table 4 CMC-induced grade III and IV non-hematological side-effects n, number of patients; n1, number of courses; FUO, fever of unknown origin; DIC, disseminated intravascular coagulation; IHD, ischemic heart disease. untreated CLL patients received two other drugs in combination with 2-CdA: cyclophosphamide and mitoxantrone (CMC programme).…”
Section: Discussionmentioning
confidence: 99%
“…10,11 These results have been confirmed recently by early clinical trials, which have shown that the combination of 2-CdA with cyclophosphamide and prednisone is feasible and active in patients with CLL and other low-grade lymphoid malignancies. 13,14 Mitoxantrone is also a useful drug in the treatment of lowgrade lymphomas and can be combined with purine analogs. [17][18][19][20] However, the advantage of such a combination in patients with refractory or relapsing disease over 2-CdA alone has not yet been proven.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation